Alcohol-Specific Computerized Interventions to Alter Cognitive Biases: A Systematic Review of Effects on Experimental Tasks, Drinking Behavior, and Neuronal Activation - Batschelet, Hallie M.; Stein, Maria; Tschuemperlin, Raphaela M.; Soravia, Leila M.; Moggi, Franz (Frontiers in Psychiatry, 2020)
Background: In patients with Alcohol use disorder, novel interventions to increase abstinence have attracted growing attention. Interventions aimed at modifying cognitive biases linked to alcohol use (i.e., cognitive bias modification (CBM)) may serve as an add-on to standard therapy. are summarized. This systematic review thoroughly aggregates existing data on the effects of three alcohol-specific computerized interventions, namely attentional bias modification (AtBM), approach bias modification (ApBM), and inhibition training (IT). In doing so, each CBM’s effects on experimental tasks assessing the relevant biases, drinking behavior, and neurophysiology are summarized. Also, the influence of drinking behavior severity and motivation to change drinking behavior are discussed. Methods: A literature search was conducted in four databases for original research articles published between 2000 and May 2019. Studies were eligible if investigating the effects of alcohol-specific computerized interventions (AtBM, ApBM, IT) on drinking behavior, bias change, and/or neurophysiology. Forty eligible articles were classified as being either a non-clinical experimental lab study (ELS) or clinical randomized-controlled trial (RCT) and summarized. Results: While AtBM seems to influence attentional bias, its effects on drinking behavior are inconsistent. As for ApBM, the best effects on drinking behavior are obtained in clinical samples. Effects of ApBM on approach bias are mixed. Interestingly, those clinical RCTs which investigated ApBM effects on bias change as well as on drinking outcome, reported consistent effects in both measures (i.e. either effects on bias and drinking or no effects). Studies on IT are limited to non-clinical samples and show inconsistent effects on drinking behavior. Considering ITs effects on implicit semantic associations, most studies do not support the conceptualization of IT as a form of memory bias modification, while reports on inhibitory effects of IT a still incomplete. Conclusions about the overall influence of drinking behavior severity are hampered by the non-uniform use of sample descriptions. Conclusions: In clinical samples, ApBM has shown more consistent beneficial effects, while evidence on AtBM is more inconsistent, and data on IT still lacks important information. Conclusions about the influence of drinking behavior severity would be facilitated by a uniform use of clearly defined sample descriptions.